Pemberdayaan Petani Pala dalam Meningkatkan Produktivitas Hasil Tanaman Pala di Distrik Pariwari Kabupaten Fakfak - Ichlazul Amal Suaery; Bayu Akbar (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
Fakfak Regency is one of the largest nutmeg producers in West Papua. Hence, the authors are interested in conducting this study entitled "Empowerment of Nutmeg Farmers in Increasing Productivity of Nutmeg Crops in Pariwari District”. The study aims to find out how to empower nutmeg farmers in Pariwari District by the Plantation Service and also to find out what are the supporting and inhibiting factors and how the Plantation Service's efforts are in empowering nutmeg farmers in Pariwari District. The research method used by the authors is qualitative. Sources of data in this study are primary and secondary data. Data collection techniques consist of interviews, observation, and documentation. The results show that the Plantation Service of Fakfak Regency has carried out its duties to empower the community of nutmeg farmers in Pariwari District. This community is a model of an empowered nutmeg farming community.